2021
DOI: 10.3390/ani11092514
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Clostridium butyricum Supplementation on Growth Performance, Intestinal Barrier Function, Immune Function, and Microbiota Diversity of Pekin Ducks

Abstract: Clostridium butyricum (C. butyricum) is increasingly being used to test the promotion of the gut health of animals. However, the modes of action for such applications for waterfowl remain unclear. Thus, we investigated whether or not intestinal barrier function, immune-related gene expression, and the diversity of the intestinal microbiota in Pekin ducks varied under C. butyricum supplementation. A total of 500 ducks were randomly assigned into five treatments supplemented with basal diets containing: either 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 49 publications
2
3
0
Order By: Relevance
“…However, in the present study, no significant differences were observed in some production performance parameters among the C. butyricum- supplemented groups. Similar to our study, supplementing feed with C. butyricum produced no significant differences in the growth performance of broilers over the whole trial period and Pekin ducks for the starter phase [ 37 , 38 ]. The plausible reasons are that the probiotic strains, dosage, or animals’ bioavailability affect their beneficial efficacy, suggesting a need for more studies on utilizing C. butyricum better.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…However, in the present study, no significant differences were observed in some production performance parameters among the C. butyricum- supplemented groups. Similar to our study, supplementing feed with C. butyricum produced no significant differences in the growth performance of broilers over the whole trial period and Pekin ducks for the starter phase [ 37 , 38 ]. The plausible reasons are that the probiotic strains, dosage, or animals’ bioavailability affect their beneficial efficacy, suggesting a need for more studies on utilizing C. butyricum better.…”
Section: Discussionsupporting
confidence: 74%
“…In addition, we noticed that the crypt depth in the antibiotic group (AM) was higher than in the 2 × 10 8 CFU/kg of C. butyricum -supplemented group at day 21 and in the 4 × 10 8 CFU/kg of C. butyricum -supplemented group at day 39. Similar manifestations were reported in the Pekin ducks and broilers, demonstrating that supplementing aureomycin into the feed has little contribution to the villus height and crypt depth in animals [ 37 , 45 ]. This study and ours collectively revealed that, regardless of whether antibiotics have a beneficial effect on intestinal morphology, hosts should be administered at the proper dosage and provided with an adequate enteral environment.…”
Section: Discussionsupporting
confidence: 58%
“…C. butyricum supplementation can modify the balance of the intestinal microbiota in aquatic animals ( 47 , 48 ). The results of this study revealed that C. butyricum G13 had significant impacts on the structure of the intestinal microbiota of mud crabs based on the alpha diversity parameters and PCoA.…”
Section: Discussionmentioning
confidence: 99%
“…Higher diversity of intestinal microbiota and changes in the secretion of some immunoglobulins and cytokines under Clostridium butyricum ( Liu et al, 2021 ). Probiotics also had a positive effect on the immune system of laying hens by increasing immunoglobulin M ( Bacillus subtilis ) ( Fathi et al, 2018 ), antibody titers against sheep red blood cells ( SRBC ), and proliferation of T and B lymphocytes ( Alaqil et al, 2020 ), and antibodies against ND ( L. acidophilus ) ( Forte et al, 2016 ).…”
Section: Pathways Of Immunostimulation and Immunomodulationmentioning
confidence: 99%